2000
DOI: 10.1046/j.1365-2141.2000.02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic abnormalities in PHA-stimulated lymphocytes from patients with Langerhans cell histiocytosis

Abstract: The aetiopathogenesis of Langerhans cell histiocytosis (LCH) is still undefined. Constitutional abnormalities in LCH have rarely been reported. One study showed chromosomal instability in lesional cells from three patients. No chromosomal studies are available on peripheral blood lymphocytes. Peripheral blood lymphocytes were analysed for the presence of chromatid and/or chromosomal breaks and structural rearrangements. A fluorescence in situ hybridization (FISH) painting technique was also applied in two case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Yet with lower viral loads, an elevated number of Merkel cell polyomavirus DNA sequences was detected in 12 LCH tissues compared with controls other than patients with dermatopathic lymphadenopathy. Previous studies of peripheral blood chromosomes showed that patients with LCH display an excess of spontaneous chromosomal breaks that are more evident during the acute phase of the disease 30 ; these findings resemble the genomic instability induced by respiratory syncytial virus (RSV), hepatitis C virus (HCV), or Epstein-Barr virus (EBV). 30,31 2.…”
Section: Lch: Inflammatory or Neoplastic?mentioning
confidence: 93%
See 1 more Smart Citation
“…Yet with lower viral loads, an elevated number of Merkel cell polyomavirus DNA sequences was detected in 12 LCH tissues compared with controls other than patients with dermatopathic lymphadenopathy. Previous studies of peripheral blood chromosomes showed that patients with LCH display an excess of spontaneous chromosomal breaks that are more evident during the acute phase of the disease 30 ; these findings resemble the genomic instability induced by respiratory syncytial virus (RSV), hepatitis C virus (HCV), or Epstein-Barr virus (EBV). 30,31 2.…”
Section: Lch: Inflammatory or Neoplastic?mentioning
confidence: 93%
“…Previous studies of peripheral blood chromosomes showed that patients with LCH display an excess of spontaneous chromosomal breaks that are more evident during the acute phase of the disease 30 ; these findings resemble the genomic instability induced by respiratory syncytial virus (RSV), hepatitis C virus (HCV), or Epstein-Barr virus (EBV). 30,31 2. What are the key signals that drive monocyte-derived DCs to form a granuloma?…”
Section: Lch: Inflammatory or Neoplastic?mentioning
confidence: 93%
“…Most cases of LCH are sporadic, but some familial cases have been reported thus suggesting a possible genetic link [2][3][4]. There are few reports of chromosomal abnormalities in this disease [5,6]. Only one clonal abnormality was identified in tissue from a LCH lesion [5].…”
Section: Introductionmentioning
confidence: 92%
“…Only one clonal abnormality was identified in tissue from a LCH lesion [5]. Peripheral blood lymphocytes have also been found to have an excess number of chromosome breaks in mitogen-stimulated cultures [6]. Another hint regarding a possible underlying genetic abnormality is the association of LCH with major congenital malformations [7].…”
Section: Introductionmentioning
confidence: 97%
“…This might be in keeping with recent evidence of association between LCH and cytokine gene polymorphism, chromosomal instability and 1% of familial clustering. 7,8,43,44 The finding of persistent control of the disease in a few patents who underwent auto-HSCT or experienced autologous reconstitution remains to be clarified.…”
Section: -39mentioning
confidence: 99%